Export-Led Growth in Chile: Assessing the Role of Export Composition in Productivity Growth - Dierk Herzer; Felicitas Nowak-Lehmann D.; Boriss Siliverstovs (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2004)
This study examines the export-led growth hypothesis using annual time series data from Chile in a production function framework. It addresses the limitations of the existing literature and focuses on the impact of manufactured and primary exports on productivity growth. In order to investigate ifin productivity, several single-equation and system cointegration techniques are applied. The estimation results can and how manufactured and primary exports affect economic growth via increases be interpreted as evidence of productivity-enhancing effects of manufactured exports and of productivity-limiting effects of primary exports.
Keywords: 330; Exportinduziertes Wachstum; Produktivität; Export; Aussenhandelsstruktur; Schätzung; Chile